South-East Asian Fortified Stone Walls: Angkor Thom (Cambodia), Ho Citadel (Vietnam) and Ratu Boko (Indonesia) - Víctor Lluís Pérez Garcia (Humaniora, 2016)
This article aims to analyze three significant examples of defensive walls from South-East Asia made of solid stone blocks (both rock as well as stone-like laterite) and provided with different but equivalent functions –a fortified imperial capital-city (Angkor Thom, in Cambodia), a fortified royal citadel (Ho Citadel, in the North of Vietnam) and a royal palace with a partly fortified appearance (Ratu Boko, in Java Island, Indonesia)–, focusing on their constructive and technical characteristics and establishing parallels between them and their closest counterparts, from China and India. We will see how their design and structure can be closely related to the fortifications of neighbouring empires, as places of origin of their strong cultural influences and, at the same time, we will try to identify the local particularities. We will pay special attention to the form of the fortified enceintes, considering the long tradition of the quadrangular plan in the walls of royal capitals, inspired in the ideal model of Chinese and Indian cities. Our research also make us think that the walls of Ratu Boko, despite their functions as symbolic limits or for retaining the soil, could also have had a defensive purpose, no matter if secondary, or at least they could be used to provide protection to the complex in case of external menace.